Effect of harvesting stages on the seed quality of lentil (Lens culinaris L.) during storage (Bangladesh Journal of Agricultural Research, 2010)
Laboratory experiments were carried out during August to September 2004 and 2005 at the Seed Technology Laboratory, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh to determine the effects of harvesting stages on the seed quality of lentil. Lentil seeds of three varieties were harvested at three stages at 7-day intervals viz. i) when the pods were yellowish with a few yellow greens (H1 stage), ii) when most of the pods were light brown with a few yellow (H2 stage), and iii) when all the pods were completely brown and dry (H3 stage). All the seeds were stored in earthen pot until conducting the laboratory study. Non-significant variation was observed in three varieties of lentil for most of the parameters studied. The highest germination percentage, root length, shoot length, seedling length and vigour index (vigour index-I and vigour index-Il) were observed in BARI Masur-4, and the lowest in BARI Masur-2. Harvesting stage had significant effect on some parameters studied. Seeds collected at the stage when most of the pods were light brown with a few yellow (H2 stage) recorded the highest germination percentage, dry weight, root length, shoot length, seedling length and vigour index (vigour index-I and vigour-Il) in both the years. BARI Masur-4 seeds collected at H2 stage recorded the highest dry weight and vigour index-I in both the years and vigour index-Il in 2004. Key Words: Lentil; harvesting stage; storage; seed quality. DOI: 10.3329/bjar.v34i4.5833Bangladesh J. Agril. Res. 34(4) : 565-576, December 2009